2019
DOI: 10.3847/1538-4357/ab2fe3
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Flux Cancellation as the Trigger Mechanism of Solar Coronal Jets

Abstract: Coronal jets are transient narrow features in the solar corona that originate from all regions of the solar disk: active regions, quiet sun, and coronal holes. Recent studies indicate that at least some coronal jets in quiet regions and coronal holes are driven by the eruption of a minifilament (Sterling et al. 2015) following flux cancellation at a magnetic neutral line (Panesar et al. 2016). We have tested the veracity of that view by examining 60 random jets in quiet regions and coronal holes using multithe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
69
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(78 citation statements)
references
References 37 publications
9
69
0
Order By: Relevance
“…To examine the magnetic field evolution quantitatively, we measured the minority-polarity flux patch of the base region that is bounded by a yellow box region of Figure 2n. Figure 4a shows a decrease in that positive flux between 18:57:37 and 19:00:37UT, presumably from flux cancelation that may have triggered the eruption of the jetlet-like event 1, as in larger jetlets and coronal jets examined by Panesar et al (2016bPanesar et al ( , 2018a and by McGlasson et al (2019). This event is similar to IRIS jetlets (Panesar et al 2018b) in that the jetlets also occurred at the edges of network flux lanes at canceling neutral lines.…”
Section: Data Setmentioning
confidence: 69%
“…To examine the magnetic field evolution quantitatively, we measured the minority-polarity flux patch of the base region that is bounded by a yellow box region of Figure 2n. Figure 4a shows a decrease in that positive flux between 18:57:37 and 19:00:37UT, presumably from flux cancelation that may have triggered the eruption of the jetlet-like event 1, as in larger jetlets and coronal jets examined by Panesar et al (2016bPanesar et al ( , 2018a and by McGlasson et al (2019). This event is similar to IRIS jetlets (Panesar et al 2018b) in that the jetlets also occurred at the edges of network flux lanes at canceling neutral lines.…”
Section: Data Setmentioning
confidence: 69%
“…Several studies show clearly that tiny coronal jets in coronal holes and quiet Sun are due to flux cancellation (Savcheva et al, 2007;Panesar et al, 2016b, Panesar et al, 2017, Panesar et al, 2018aMcGlasson et al, 2019). In coronal holes, converging flows toward the boundary of super-granule with mixed polarities leading to cancelling flux was found to be a favorable solution to explain the onset of jets (Young and Muglach, 2014;Muglach, 2021).…”
Section: Flux Cancellationmentioning
confidence: 98%
“…Panesar et al [98] argued that the reason for flux emergence not directly causing jets is because the speed of emergence is seldom, if ever, fast enough. The emerging-reconnection scenario was challenged by the discovery of blowout jets that often involve the eruption of mini-filaments or filament channels [36,62,63,69,97] in association with flux cancellations [44,66,68,247,[304][305][306][307][308], and the cool component of blowout jets is actually the erupting filament material itself [44,63,69] rather than chromospheric material carried up by the emerging flux and accelerated by the show the direction of movement of the magnetic field lines, and features including the X-point, slow and fast shocks, and cool and hot jets are indicated [140].…”
Section: (A) Emerging-reconnection Modelmentioning
confidence: 99%
“…Panesar et al [98] argued that the reason for flux emergence not directly causing jets is because the speed of emergence is seldom, if ever, fast enough. The emerging-reconnection scenario was challenged by the discovery of blowout jets that often involve the eruption of mini-filaments or filament channels [36,62,63,69,97] in association with flux cancellations [44,66,68,247,304–308], and the cool component of blowout jets is actually the erupting filament material itself [44,63,69] rather than chromospheric material carried up by the emerging flux and accelerated by the magnetic tension force as proposed in the emerging-reconnection model [129]. In a statistical study of 27 equatorial coronal hole jets, Kumar et al [97] found that six jets (22%) were apparently associated with flux cancellations, while the remaining events did not show measurable flux emergence or cancellation associated with the eruption.…”
Section: Physical Interpretation and Modellingmentioning
confidence: 99%